1996
DOI: 10.1200/jco.1996.14.6.1903
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic monitoring of continuous infusion etoposide in small-cell lung cancer.

Abstract: Therapeutic monitoring of infusional etoposide is feasible and dramatically reduces interpatient pharmacokinetic variability. Although this was a small nonrandomized trial, the observation of different hematologic toxicity at the two starting concentrations but similar antitumor activity further suggests that these effects may be associated with different plasma etoposide concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…This approach has yielded a decrease in intrapatient and interpatient variability in haematological toxicity in patients treated with i.v. etoposide [40,41]. TDM-guided dose individualization of methotrexate, teniposide and cytarabine has permitted the safe increase drug exposure in children with leukaemia [42], resulting in a signi®cant improvement in disease free as compared with conventional therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has yielded a decrease in intrapatient and interpatient variability in haematological toxicity in patients treated with i.v. etoposide [40,41]. TDM-guided dose individualization of methotrexate, teniposide and cytarabine has permitted the safe increase drug exposure in children with leukaemia [42], resulting in a signi®cant improvement in disease free as compared with conventional therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This patient had a [5LCr]EDTA clearance, which was at the bottom of the normal range (59 ml min-' m-2) and the longest [5'Cr]EDTA elimination half-life (114 min vs 77±23 min), although no overt signs of renal impairment. It seems likely that the reduced interpatient pharmacokinetic variability seen in this group of patients was due to the fact that only one child had previously received cisplatin, as cisplatin therapy has previously been shown to predict for reduced etoposide clearance (Pfluger et al, 1987(Pfluger et al, , 1993Relling et al, 1994 Previous studies involving targeted dosing with etoposide using limited sampling methods have involved the administration of etoposide as a continuous infusion over 3 or 5 days (Ratain et al, 1989(Ratain et al, , 1991Joel et al, 1996). In addition, English et al (1996) reported two anephric paediatric patients in whom targeted dosing with both etoposide and carboplatin was possible using detailed pharmacokinetic sampling over three doses.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Joel et al (1996) have reported the results of a pharmacokinetically based dose escalation study of etoposide given intravenously as a continuous infusion over 5 days. Dose modifications after 18 and 66 h were performed on the basis of plasma etoposide concentrations in order to achieve a target level of 2, 3, 4 or 5 ,ug ml-'.…”
Section: Discussionmentioning
confidence: 99%
“…On the morning of day 7 (18 h after the start of the infusion) and on day 9 of each cycle, peripheral venous blood samples were drawn for determination of total plasma etoposide levels, as described previously (Harvey et al, 1985a;Joel et al, 1996Joel et al, , 1998. Plasma standards covering the range 0.5 -5.0 mg ml À1 were used; patient samples were run in duplicate, with quality control samples at two concentrations (1.25 and 3.5 mg ml À1 ).…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…The initial infusion rate was calculated and adjusted according to measured plasma etoposide concentrations (Joel et al, 1996).…”
Section: à2mentioning
confidence: 99%